Ultrasounds versus fluoroscopy guidance for axillary vein puncture for cardiac devices implantation : a multicenter randomized comparison. (19th May 2022) - Bun, S-S; Taghji, P; Massoure, PL; Roche, N; Squara, F; Scarlatti, D; Moceri, P; Deharo, JC; Ferrari, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Axillary vein (AV) puncture, an emerging route for cardiac implantable electronic devices (CIED), can be performed under ultrasounds (US) or fluoroscopic (Fluo) guidance. Objective: To compare US to fluroroscopy-guided AV puncture in a multicenter randomized controlled trial. Methods: Consecutive patients admitted for CIED (first implant or upgrade, including resynchronization therapy) intervention were prospectively randomized between US or Fluo guidance for AV puncture in the three participating centers. Access performances, radiation exposure and complications were compared in both groups. Results: 102 patients were included (n = 51 patients per group). The two groups had similar characteristics concerning age (79.4 ± 10 years), and LVEF (47 ± 17%). 92 leads were implanted in both groups. AV catheterization was successful in 50/51 (98 %) in the US group versus 49/51 in the Fluo group (96 %, p = 0.56). AV access time and procedure time were not different between the two groups, respectively (156 ± 274 in the US group versus 137 ± 151 sec, p = 0.66; 54 ± 24 versus 61 ± 26 min; p = 0.13). Total fluoroscopy time (FT) and dose-area product were respectively lower in the US group, but without reaching significance: 197 ± 231 versus 247 ± 293 sec, p = 0.32; 0.39 ± 0.95 versus 0.75 ± 1.58 mGy.m², p = 0.14. FT for AV access was significantly higher in the Fluo group (51 ± 55 sec versus 0, p < 0.0001). There were two complications in each group during the 9 ± 6 months follow-up. Conclusion: Our study demonstrates that both US and fluoroscopy-guided AV catheterization for CIED are highly effective and safe techniques. Despite similar AV access time, compared to fluo guidance, US reduce time radiation exposure by 20 %.